Partial purification and characterization of a superoxide distimutase (SOD1) from black tiger shrimps Penaeus monodon - Hien, Tran Minh; Hong Loan, Nguyen Thi; Quynh, Trinh Dinh; Trang, Ngo Thi; Lua, Dang Thi; Nghia, Phan Tuan (Academia Journal of Biology, 2020)
Superroxide dismutase (SOD, EC.1.15.1.1) is the enzyme which dismutates superoxide radicals and plays an important role in protection of living cells against oxidative stress. SOD is also involved in immune response in shrimps. In this study, it was found that the total SOD activity of black tiger shrimp muscular tissues is 10 fold higher than that of the haemolymph, however, the specific activity of SOD in the shrimp haemolymph is 9.2 fold higher than that of muscular tissues. By using active gel electrophoresis, 2 different SOD forms were found in black tiger shrimps (one in muscular tissues and two in haemolymph).Using DE-52 cellulose and Q-Sepharose ion exchange column chromatography, one SOD (SOD1) from black tiger shrimp haemolymph was partially purified, and its purity was 31.2 times higher than that of the starting haemolymph. The SOD1 was shown to have mainly one protein band of approximately 24 kDa on SDS-PAGE. SOD1 was most active at 45oC and pH of 5.5. At a concentration of 5 mM, Mn2+ strongly activated SOD1 (up 200% activity), Ca2+ và Zn2+ could increase approximately 20% activity while Cu2+ inhibited more than 60% ativity of the enzyme.